Preparation and Properties of High Performance Multilayered PANi/PMMA/PPG-b-PEG-b-PPG/FGHMDA Nanocomposites via in Situ Polymerization. Issue 3 (11th February 2019) - Naz, Asima; Sattar, Rabia; Siddiq, Muhammad
ABSTRACT: In this attempt, novel conjugated polymer/graphite nanocomposites with exposed surface area were fabricated by in situ polymerization using polyaniline, poly(methyl methacrylate) and poly(propylene glycol)-block-poly(ethylene glycol) block- poly(propylene glycol) as matrices and functionalized graphite as a filler. Structural and morphological analysis revealed the modification of graphite as well as oxidative polymerization of numerous matrices over the surface of modified graphite ensuing multilayered nanocomposites. The increased values of Tg (59 and 103°C) obtained from thermal analysis reflect the improved thermal stability of prepared nanocomposites and exhibit better adsorption capacity (35.5cm 3 /g). Maximum electrical conductivity (7.4 S/cm) was also observed for multilayered nanocomposite. GRAPHICAL ABSTRACT: